User Interface Evaluation in Metvaerse Gamelan Virtual Reality Using Heuristics Evaluation Method - Eric Jonathan; Clara Hetty Primasari; Thomas Adi Purnomo Sidhi; Yohanes Priadi Wibisono; Djoko Budiyanto Setyohadi; Mutiara Cininta (LPPM UTDI (d.h STMIK AKAKOM) Yogyakarta, 2022)
The increase in information technology in today's era makes the availability of Augmented Reality or Virtual Reality enabled devices, which can become a gateway to exploring various applications, increase. For the example is the virtual reality application of Gamelan Slenthem, which is currently being developed with the aim of making Indonesian cultural musical instruments. Even though what is developed is not an application or an ordinary website, the user interface is still one of the most important stages in the development of an augmented reality or virtual reality application. Every information technology has an interface that can be a link between the user and the technology itself. The interface is influenced by needs, and information technology has a design that makes it easy for users to operate information technology and can make users feel comfortable using the application or technology. In this study, we will use heuristic evaluation to evaluate the application of the virtual reality gamelan metaverse game. Heuristic evaluation itself is a method of evaluating user interfaces and usability that can be used to determine the extent to which a system is used by users to achieve certain goals effectively, efficiently, and satisfactorily. This research focuses on evaluating the use of heuristics in user interface design based on usability aspects through observation and interviews with users.